Effects of thermal treatments on chilling injury and shelf life time of citrus reticulata blanco1 (2019)
The ‘Arrayana’ mandarin (Citrus reticulata Blanco) is considered the variety most widely grown in Colombia. Despite being a non-climacteric fruit, it has a short postharvest life. In order to evaluate the effects of thermal treatments on the chilling injury and shelf life time of this cultivar, ripe fruits were selected and submitted to the following treatments: non-treated fruit (control); hot water at 50 ºC for 5 min; hot water at 53 ºC for 3 min; intermittent warming in 8-day cycles at 2 ºC + 1 day at 18 ºC; and intermittent warming in 12-day cycles at 2 ºC + 1 day at 18 ºC. The fruits were stored at 2 ºC for 40 days and then left for one week at room temperature. The thermal treatments decreased the chilling injury in the mandarin fruits during the shelf life time, with the intermittent warming treatments being the most favourable ones (mainly in cycles of 12 days at 2 ºC + 1 day at 18 ºC), because, besides decreasing the chilling injuries and electrolytes leakage, they promoted a higher carotenoid biosynthesis and epidermis colouring, without negative effects on the fruit internal quality.